Preparation method of carbon nanotube-graphene / copper-based composite material with discontinuous network structure
By forming a discontinuous CNT-RGO network in the copper-based composite material, the problem of difficult to maintain toughness and conductivity when the existing materials are improved is solved, and the preparation of copper-based composite materials with high mechanical properties and conductivity is achieved.
Patent Information
- Application Number
- CN202510017428.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-11
AI Technical Summary
While the existing copper-based composite materials improve strength, toughness and conductivity are difficult to maintain, and the interface of the reinforcement body and the substrate are insufficient, resulting in limited strengthening efficiency.
The CNT-RGO network is formed by a carbon nanotube-graphene/copper-based composite material preparation method with a discontinuous network structure, and the mechanical properties and conductivity of the Cu matrix are enhanced by acidification treatment, ultrasonic dispersion, ball milling and reduction.
It realizes the high yield strength, tensile strength and elongation of break of copper-based composite materials, and has a stable process and simple equipment, which is suitable for the preparation of other metal-based composite materials.
Smart Images

Figure CN119800144A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a carbon nanotube-graphene / copper-based composite material with a discontinuous network structure, and belongs to the technical field of metal-based composite material preparation. Background Art
[0002] Copper-based composite materials are composite materials that are based on metallic copper (Cu) or copper alloys and are artificially combined with one or more metal or non-metal reinforcements. Compared with copper and copper alloys, copper-based composite materials have higher specific strength, specific modulus, low thermal expansion coefficient and other excellent properties, which can fill the performance shortcomings of pure copper to meet the material performance requirements of various industries. However, the inherent shortcoming of copper-based composite materials is that their strength is inversely proportional to toughness and conductivity, that is, an increase in strength will lead to a decrease in the toughness and conductivity of the composite material. Nowadays, various fields are promoting the rapid development of the performance of copper-based composite materials, while ensuring good strength without excessive loss of material toughness or conductivity.
[0003] Nanomaterials, including one-dimensional carbon nanotubes (CNTs), two-dimensional graphene oxide (GO) and reduced graphene oxide (RGO), all play a particularly important role in the field of copper-based composites, and have a wide range of demands and good development prospects. CNT is an ideal reinforcement material with excellent mechanical, electrical and thermal properties. Its tensile strength is about 100 times that of high-strength steel, its density is only 1 / 6 of that of steel, and its conductivity is about 10 2 S / cm, current carrying capacity up to 10 9 A / cm 2 , thermal conductivity reaches 3.0kW / (m·K); GO is obtained by oxidation treatment of graphene, and some oxygen-containing functional groups are successfully introduced into the graphene surface; but due to the poor dispersion and weak interface bonding of CNT and GO in the Cu matrix, the expected strengthening efficiency is not obtained.
[0004] At present, the mainstream preparation methods of CNTs reinforced copper-based composites include molecular-level blending, flaky powder metallurgy, electrodeposition and other preparation methods; in terms of improving the interface bonding between the reinforcement and the matrix, there are surface modification of carbon nanotubes, introduction of in-situ generated carbides and small-angle grain boundaries at the interface between CNT and Cu to improve their interface bonding, but the strengthening efficiency of the reinforcement is still limited after using these methods; therefore, high-performance copper-based composites can be prepared starting from the microstructure design of the reinforcement. Summary of the invention
[0005] The present invention provides a method for preparing a carbon nanotube-graphene / copper-based composite material with a discontinuous network structure, wherein a discontinuous CNT-RGO network is formed in the composite material, and a copper-based composite material with good comprehensive performance is obtained through the synergistic effect of CNT and RGO; a method for preparing a carbon nanotube-graphene / copper-based composite material with a discontinuous network structure comprises the following steps:
[0006] (1) Placing the carbon nanotubes (CNT) in a mixed solution of concentrated sulfuric acid and concentrated nitric acid for acidification to obtain acid-treated carbon nanotubes (CNT).
[0007] (2) Using graphite powder as raw material, graphene oxide GO is prepared by oxidation exfoliation method.
[0008] (3) ultrasonically dispersing the acid-treated carbon nanotubes CNT obtained in step (1) and the graphene oxide GO prepared in step (2) in water to obtain dispersions of the acid-treated carbon nanotubes CNT and the graphene oxide GO, mixing the dispersions of the acid-treated carbon nanotubes CNT and the graphene oxide GO and stirring them to obtain a CNT-GO suspension, and filtering and drying the product to obtain a CNT-GO hybrid.
[0009] (4) The spherical copper powder is ball-milled in ethanol for the first time, and then the CNT-GO hybrid treated in step (3) is mixed with the ball-milled Cu powder and ball-milled for a second time to obtain a composite powder, and then the composite powder is reduced in an Ar-H2 mixed atmosphere to obtain a CNT-RGO / Cu composite powder.
[0010] (5) The CNT-RGO / Cu composite powder prepared in step (4) is subjected to spark plasma sintering to obtain a CNT-RGO / Cu composite material, which is a carbon nanotube-graphene / copper-based composite material.
[0011] Preferably, in step (1), the purity of the carbon nanotubes CNT used is not less than 99%, the volume ratio of concentrated sulfuric acid to concentrated nitric acid is (3:1) to (5:1), and the acidification treatment time is 8 to 12 hours.
[0012] Preferably, in step (2), the purity of the graphite powder used is not less than 99%.
[0013] Preferably, in the step (3), the volume ratio of the acid-treated carbon nanotubes CNT to the graphene oxide GO is (3:1) to (6:1).
[0014] Preferably, in step (3), the ultrasonic dispersion treatment time is 1 to 2 hours, the ultrasonic dispersion power is 10 kW, and the stirring time is 1 to 3 hours.
[0015] Preferably, in the step (4), the average particle diameter of the copper powder used is 1 to 3 μm, and the conditions for the first ball milling are: the ball-to-material ratio is 10:1, the diameter of the stainless steel balls is 5 to 7 mm, the ball milling speed is 250 to 350 r / min, and the ball milling time is 9 to 11 h; the conditions for the second ball milling are: the ball-to-material ratio is 10:1, the diameter of the stainless steel balls is 5 to 7 mm, the ball milling speed is 250 to 350 r / min, the ball milling time is 4.5 to 5.5 h, and the speed is 250 to 350 r / min.
[0016] Preferably, in step (4), the volume of CNT-GO accounts for 0.75% to 1.5% of the total volume of the CNT-RGO / Cu composite powder.
[0017] Preferably, in step (4), the reduction temperature is 250-300° C. and the reduction time is 8-12 h.
[0018] Preferably, in the step (5), the temperature during spark plasma sintering is set to 700-800° C., the heating rate is 100° C. / min, and the holding time is 10-15 min.
[0019] The principle of the present invention is as follows: by reducing the composite powder after ball milling, CNT-GO is converted into CNT-RGO (carbon nanotube-reduced graphene oxide) during the reduction process to obtain CNT-RGO powder, and the CNT-RGO is formed into a whole through the π-π bond. After the sintering process, the CNT-RGO is closely linked together, has a strong interface bonding and provides good load transfer efficiency, combined with the subsequent sintering process control, thereby improving the mechanical properties of the composite material.
[0020] Beneficial effects of the present invention:
[0021] (1) The present invention combines ball-milled flaky Cu powder with the reinforcement. Compared with the original spherical powder, the flaky Cu powder has more planar areas and can increase the attachment area of CNT and GO.
[0022] (2) CNT and RGO form a whole through strong π-π bonds. After sintering, the CNT-RGO mixed structure with different structures is closely linked together to form a discontinuous network structure. CNT and RGO are interconnected and together serve as reinforcements to strengthen Cu-based composites, which can effectively improve the comprehensive performance of the material.
[0023] (3) The process of the present invention is stable and the equipment used is simple. The idea of improving the strengthening efficiency of the reinforcement body by designing the reinforcement body structure can also be applied to the preparation process of other metal-based composite materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1This is a high-magnification SEM image of the non-continuous network structure CNT-RGO / Cu composite material in Example 2 of the present invention.
[0025] Figure 2 These are low-magnification bright field (a) and dark field (b) TEM images of the discontinuous network structure CNT-RGO / Cu composite material in Example 2 of the present invention.
[0026] Figure 3 This is a tensile fracture morphology of the non-continuous network structure CNT-RGO / Cu composite material in Example 2 of the present invention. DETAILED DESCRIPTION
[0027] In order to facilitate the understanding of the present invention, the present invention will be described in more comprehensive and detailed manner in conjunction with the accompanying drawings and preferred embodiments of the specification, but the protection scope of the present invention is not limited to the following specific embodiments; unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the protection scope of the present invention.
[0028] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0029] Example 1
[0030] A method for preparing a carbon nanotube-graphene / copper-based composite material with a discontinuous network structure, comprising the following specific steps:
[0031] (1) The carbon nanotubes (CNT) are placed in a mixed solution of concentrated H2SO4 and concentrated HNO3 (the volume ratio of concentrated H2SO4 to concentrated HNO3 is 3:1) and subjected to acid treatment for 10 hours to obtain acid-treated carbon nanotubes (CNT).
[0032] (2) Graphite powder is cracked into graphene oxide GO by oxidation exfoliation method.
[0033] (3) The acid-treated carbon nanotubes CNT obtained in step (1) and the graphene oxide GO obtained in step (2) are respectively placed in deionized water, and the ultrasonic dispersion treatment time is 1 hour, and the ultrasonic dispersion power is 10 kW, wherein the volume ratio of the acid-treated carbon nanotubes CNT and the graphene oxide GO is 6:1 (there is no requirement for the amount of deionized water used as a solvent, as long as the carbon nanotubes CNT and the graphene oxide GO are fully dispersed), and then the dispersion of the acid-treated carbon nanotubes CNT and the dispersion of the graphene oxide GO are mixed, and then magnetic stirring is performed for 2 hours to obtain a prepared CNT-GO mixed suspension, and then the suspension is filtered and dried to obtain a CNT-GO hybrid.
[0034] (4) 20 g of spherical Cu powder (average particle diameter is about 1-3 μm) is placed in a 500 ml ball mill, and 200 g of steel balls are added to the ball mill as ball milling media, that is, the ball-to-material ratio is 10:1, the diameter of the stainless steel balls used is 6 mm, and ethanol is added as a process control agent until the powder and the steel balls are submerged, and low-speed ball milling is performed at a ball milling speed of 300 rpm. After the ball milling time is 10 hours, the CNT-GO hybrid prepared in step (3) is added to the ball mill and ball milled together with the Cu powder at a ball milling speed of 300 rpm for 5 hours. After filtering and drying, a CNT-GO / Cu composite powder is obtained, wherein the volume fraction of the CNT-GO powder is 0.75% of the volume of the CNT-GO / Cu composite powder.
[0035] (5) The CNT-GO / Cu composite powder obtained in step (4) is reduced in a mixed atmosphere of Ar-5% H2 using a tubular furnace at a temperature of 250°C for 10 hours. During the reduction process, GO is converted into RGO to obtain a CNT-RGO / Cu composite powder.
[0036] (6) The CNT-RGO / Cu composite powder obtained in step (5) is subjected to spark plasma sintering. During sintering, the heating rate is set to 100°C / min, the sintering temperature is 750°C, and the holding time is 10min; then the sintered composite material is polished to obtain a CNT-RGO / Cu composite material.
[0037] The yield strength of the CNT-GO / Cu composite material prepared in this example is 242 MPa, the tensile strength is 308 MPa, and the elongation at break is 9.2%.
[0038] Example 2
[0039] A method for preparing a carbon nanotube-graphene / copper-based composite material with a discontinuous network structure, comprising the following specific steps:
[0040] (1) The carbon nanotubes (CNT) are placed in a mixed solution of concentrated H2SO4 and concentrated HNO3 (the volume ratio of concentrated H2SO4 to concentrated HNO3 is 3:1) and subjected to acid treatment for 10 hours to obtain acid-treated carbon nanotubes (CNT).
[0041] (2) Graphite powder is cracked into graphene oxide GO by oxidation exfoliation method.
[0042] (3) The acid-treated carbon nanotubes CNT obtained in step (1) and the graphene oxide GO obtained in step (2) are respectively placed in deionized water, the ultrasonic dispersion treatment time is 1 hour, the ultrasonic dispersion power is 10 kW, the volume ratio of CNT to GO is 6:1, and then the mixed solution of CNT and GO is added together, and then magnetic stirring is performed for 2 hours to obtain a prepared CNT-GO suspension, and then the suspension is filtered and dried to obtain a CNT-GO hybrid.
[0043] (4) 20 g of spherical Cu powder (average particle diameter is about 1-3 μm) is mixed and placed in a 500 ml ball mill, and 200 g of steel balls are added to the ball mill as ball milling media, that is, the ball-to-material ratio is 10:1, the diameter of the stainless steel balls used is 6 mm, and ethanol is added as a process control agent until the powder and the steel balls are submerged, and low-speed ball milling is performed, the ball milling speed is 300 rpm, and the ball milling time is 10 h; the CNT-GO hybrid prepared in step (3) is added to the ball mill and ball milled together with the Cu powder, the ball milling speed is 300 rpm, and the ball milling time is 5 h, and then filtered and dried to obtain a CNT-GO / Cu composite powder, wherein the volume fraction of the CNT-GO powder is 1.5% of the volume of the CNT-GO / Cu composite powder.
[0044] (5) The CNT-GO / Cu composite powder obtained in step (4) is reduced in a mixed atmosphere of Ar-5% H2 using a tubular furnace at a temperature of 250°C for 10 hours. During the reduction process, GO is converted into RGO, and then a CNT-RGO / Cu composite powder is obtained.
[0045] (6) The CNT-RGO / Cu composite powder obtained in step (5) is subjected to spark plasma sintering. During sintering, the heating rate is set to 100°C / min, the sintering temperature is 750°C, and the holding time is 10min; then the sintered composite material is polished to obtain a CNT-RGO / Cu composite material.
[0046] The high-magnification SEM image of the discontinuous network structure CNT-RGO / Cu composite material in this embodiment is as follows: Figure 1 As shown, it can be seen that CNT and RGO are closely connected and form some network nodes. CNT is connected and tightly wrapped by the sheet-like RGO, forming an interconnected network structure but not continuous. Figure 2 The yellow dotted line in the TEM image also shows that the CNT-RGO hybrid structure has been evenly dispersed in the Cu matrix, which also clearly demonstrates that a non-continuous network structure has been formed between CNT and RGO.
[0047] The yield strength of the CNT-RGO / Cu composite material prepared in this embodiment is 308 MPa, the tensile strength is 412 MPa, and the elongation at break is 4.8%. Figure 3 In the SEM image of the composite material fracture prepared in this example, the network structure is clearly visible, and the failure mode of the reinforcement in the composite material is pull-off. This mode can enhance load transfer and obtain better performance.
[0048] Example 3
[0049] A method for preparing a carbon nanotube-graphene / copper-based composite material with a discontinuous network structure, comprising the following specific steps:
[0050] (1) The carbon nanotubes (CNT) are placed in a mixed solution of concentrated H2SO4 and concentrated HNO3 (the volume ratio of concentrated H2SO4 to concentrated HNO3 is 4:1) and subjected to acid treatment for 8 hours to obtain acid-treated carbon nanotubes (CNT).
[0051] (2) Graphite powder is cracked into graphene oxide GO by oxidation exfoliation method.
[0052] (3) The acid-treated carbon nanotubes CNT obtained in step (1) and the graphene oxide GO obtained in step (2) are respectively placed in deionized water, and the ultrasonic dispersion treatment time is 2 hours, and the ultrasonic dispersion power is 10 kW, wherein the volume ratio of the acid-treated carbon nanotubes CNT and the graphene oxide GO is 3:1, and then the dispersion of the acid-treated carbon nanotubes CNT and the dispersion of the graphene oxide GO are mixed, and then magnetic stirring is performed for 3 hours to obtain a prepared CNT-GO suspension, and then the suspension is filtered and dried to obtain a CNT-GO hybrid.
[0053] (4) 20 g of spherical Cu powder (average particle diameter is about 1-3 μm) is mixed and placed in a 500 ml ball mill, and 200 g of steel balls are added to the ball mill as ball milling media, that is, the ball-to-material ratio is 10:1, and the diameter of the stainless steel balls used is 6 mm. Ethanol is added as a process control agent until the powder and the steel balls are submerged, and low-speed ball milling is performed at a ball milling speed of 250 rpm for 11 h. The CNT-GO hybrid prepared in step (3) is added to the ball mill and ball milled together with the Cu powder at a ball milling speed of 350 rpm for 4.5 h. After filtering and drying, a CNT-GO / Cu composite powder is obtained, in which the volume fraction of the CNT-GO powder is 1.5% of the CNT-GO / Cu composite powder.
[0054] (5) The CNT-GO / Cu composite powder obtained in step (4) is reduced in a mixed atmosphere of Ar-5% H2 using a tubular furnace at a temperature of 250°C for 12 hours. During the reduction process, GO is converted into RGO to obtain a CNT-RGO / Cu composite powder.
[0055] (6) The CNT-RGO / Cu composite powder obtained in step (5) is subjected to spark plasma sintering. During sintering, the heating rate is set to 100°C / min, the sintering temperature is 700°C, and the holding time is 10min; then the sintered composite material is polished to obtain a CNT-RGO / Cu composite material.
[0056] The yield strength of the discontinuous network structure CNT-RGO / Cu composite material prepared in this embodiment is 296 MPa, the tensile strength is 396 MPa, and the elongation at break is 5.7%.
[0057] Example 4
[0058] A method for preparing a carbon nanotube-graphene / copper-based composite material with a discontinuous network structure, comprising the following specific steps:
[0059] (1) The carbon nanotubes (CNT) are placed in a mixed solution of concentrated H2SO4 and concentrated HNO3 (the volume ratio of concentrated H2SO4 to concentrated HNO3 is 5:1) and subjected to acid treatment for 12 hours to obtain acid-treated carbon nanotubes (CNT).
[0060] (2) Graphite powder is cracked into graphene oxide GO by oxidation exfoliation method.
[0061] (3) The acid-treated carbon nanotubes CNT obtained in step (1) and the graphene oxide GO obtained in step (2) are respectively placed in deionized water, and ultrasonically treated for 2 hours. The power of ultrasonic dispersion is 10 kW, wherein the volume ratio of the acid-treated carbon nanotubes CNT and the graphene oxide GO is 4:1, and then the dispersion of the acid-treated carbon nanotubes CNT and the dispersion of the graphene oxide GO are mixed, and then magnetic stirring is performed for 1 hour to obtain a prepared CNT-GO suspension, and then the suspension is filtered and dried to obtain a CNT-GO hybrid.
[0062] (4) 20 g of spherical Cu powder (average particle diameter is about 1-3 μm) is mixed and placed in a 500 ml ball mill, and 200 g of steel balls are added to the ball mill as ball milling media, that is, the ball-to-material ratio is 10:1, the diameter of the stainless steel balls used is 6 mm, and ethanol is added as a process control agent until the powder and the steel balls are submerged, and low-speed ball milling is performed at a ball milling speed of 350 rpm for 9 h. The CNT-GO hybrid prepared in step (3) is added to the ball mill and ball milled together with the Cu powder at a ball milling speed of 250 rpm for 5.5 h. After filtering and drying, a CNT-GO / Cu composite powder is obtained, in which the volume fraction of the CNT-GO powder is 1.5% of the CNT-GO / Cu composite powder.
[0063] (5) The CNT-GO / Cu composite powder obtained in step (4) is reduced in a mixed atmosphere of Ar-5% H2 using a tubular furnace at a temperature of 300°C for 8 hours. During the reduction process, GO is converted into RGO to obtain a CNT-RGO / Cu composite powder.
[0064] (6) The CNT-RGO / Cu composite powder obtained in step (4) is subjected to spark plasma sintering. During sintering, the heating rate is set to 100°C / min, the sintering temperature is 800°C, and the holding time is 15min; then the sintered composite material is polished to obtain a CNT-RGO / Cu composite material.
[0065] The yield strength of the non-continuous network structure CNT-RGO / Cu composite material prepared in this embodiment is 273 MPa, the tensile strength is 350 MPa, and the elongation at break is 3.3%.
[0066] Comparative Example 1
[0067] This example uses the same process as Example 2 to prepare the CNT / Cu composite material.
[0068] (1) The carbon nanotubes (CNT) are placed in a mixed solution of concentrated H2SO4 and concentrated HNO3 (the volume ratio of concentrated H2SO4 to concentrated HNO3 is 3:1) and subjected to acid treatment for 10 hours to obtain acid-treated carbon nanotubes (CNT).
[0069] (2) The acidified carbon nanotubes (CNT) obtained in step (1) are placed in deionized water for ultrasonic treatment for 2 h, with the ultrasonic dispersion power being 10 kW to obtain a prepared acidified carbon nanotube (CNT) suspension, and the suspension is filtered and dried to obtain the acidified CNT.
[0070] (3) 20g of spherical Cu powder (average particle diameter of about 1-3μm) was mixed and placed in a 500ml ball mill, and 200g of steel balls were added to the ball mill as the ball milling medium, i.e., the ball-to-material ratio was 10:1, and ethanol was added as a process control agent until the powder and the steel balls were submerged, and low-speed ball milling was performed, the ball milling speed was 300rpm, and the ball milling time was 10h. The acidified CNT and Cu powder prepared in step (2) were ball milled together, the stainless steel balls used had a diameter of 6mm, the ball milling speed was 300rpm, and the ball milling time was 5h, and then filtered and dried to obtain a CNT / Cu composite powder, wherein the volume fraction of CNT was 1.5% of the CNT / Cu composite powder.
[0071] (4) The composite powder obtained in step (3) is reduced in an Ar-5% H2 atmosphere using a tubular furnace at a temperature of 250°C for 10 h to obtain a CNT / Cu composite powder.
[0072] (5) The composite powder obtained in step (4) is subjected to spark plasma sintering. During sintering, the heating rate is set to 100°C / min, the sintering temperature is 750°C, and the holding time is 10min; then the sintered composite material is polished to obtain a CNT / Cu composite material.
[0073] In the CNT / Cu composite material, individual CNTs are evenly dispersed in the Cu matrix, and the reinforcements are isolated from each other and no interconnected network structure is generated.
[0074] The composite material prepared in this embodiment has a yield strength of 176 MPa, a tensile strength of 231 MPa, and an elongation at break of 10.9%.
[0075] By comparison with Example 2, it can be seen that the yield strength and tensile strength of the composite material reinforced with the CNT-RGO mixture are significantly higher than those of the single CNT / Cu composite material. During the tensile deformation process, CNT and RGO are bridged as a whole, thereby strengthening the Cu matrix, while CNT does not do this.
[0076] Comparative Example 2
[0077] This example uses the same process as Example 2 to prepare the RGO / Cu composite material.
[0078] (1) Graphite powder is cracked into graphene oxide (GO) by an oxidative exfoliation method, and the graphene oxide (GO) is placed in deionized water for ultrasonic treatment for 2 h. The power of ultrasonic dispersion is 10 kW to obtain a prepared graphene oxide (GO) suspension. The graphene oxide (GO) suspension is then filtered and dried to obtain dissociated graphene oxide (GO).
[0079] (2) 20g of spherical Cu powder (average particle diameter of about 1-3μm) was mixed and placed in a 500ml ball mill, and 200g of steel balls were added as ball milling media, i.e., the ball-to-material ratio was 10:1, and the diameter of the stainless steel balls used was 6mm. Ethanol was added as a process control agent until the powder and the steel balls were submerged, and low-speed ball milling was performed, the ball milling speed was 300rpm, and the ball milling time was 10h. The dissociated graphene oxide GO prepared in step (1) was ball milled with Cu powder, the ball milling speed was 300rpm, and the ball milling time was 5h, and then filtered and dried to obtain GO / Cu composite powder, wherein the volume fraction of the dissociated graphene oxide GO was 1.5% of the volume of the GO / Cu composite powder.
[0080] (3) The composite powder obtained in step (2) is reduced in a mixed atmosphere of Ar-5% H2 using a tubular furnace at a temperature of 250°C for 10 hours. During the reduction process, GO is converted into RGO, and then an RGO / Cu composite powder is obtained.
[0081] (4) The composite powder obtained in step (3) is subjected to spark plasma sintering. During sintering, the heating rate is set to 100°C / min, the sintering temperature is 750°C, and the holding time is 10min; then the sintered composite material is polished to obtain the RGO / Cu composite material.
[0082] The composite material prepared in this embodiment has a yield strength of 214 MPa, a tensile strength of 263 MPa, and an elongation at break of 8.5%.
[0083] By comparison with Example 2, it can be seen that the yield strength and tensile strength of the composite material reinforced with the CNT-RGO mixture are significantly higher than those of the single RGO / Cu composite material.
[0084] Comparative Example 3
[0085] This example uses the same process to prepare pure Cu
[0086] (1) 20 g of spherical Cu powder (average particle diameter is about 1-3 μm) was mixed and placed in a 500 ml ball mill, and 200 g of steel balls were added to the ball mill as the ball milling medium, that is, the ball-to-material ratio was 10:1, and the diameter of the stainless steel balls used was 6 mm. Ethanol was added as a process control agent until it covered the powder and the steel balls, and low-speed ball milling was performed. The ball milling speed was 300 rpm and the ball milling time was 10 h.
[0087] (2) The composite powder obtained in step (1) is subjected to spark plasma sintering. During sintering, the heating rate is set to 100° C. / min, the sintering temperature is 750° C., and the holding time is 10 min.
[0088] The pure Cu prepared in this embodiment has a yield strength of 137 MPa, a tensile strength of 202 MPa, and an elongation at break of 24.5%.
[0089] By comparison with Example 2, it can be seen that the yield strength and tensile strength of the composite material reinforced with the CNT-RGO mixture are significantly higher than those of pure Cu.
Claims
1. A method for preparing a carbon nanotube-graphene / copper-based composite material having a discontinuous network structure, characterized in that: The following steps are involved: (1) placing carbon nanotubes (CNT) in a mixed solution of concentrated sulfuric acid and concentrated nitric acid for acidification to obtain acid-treated carbon nanotubes (CNT); (2) Using graphite powder as raw material, graphene oxide GO is prepared by oxidation exfoliation method; (3) ultrasonically dispersing the acid-treated carbon nanotubes CNT obtained in step (1) and the graphene oxide GO prepared in step (2) in water to obtain dispersions of the acid-treated carbon nanotubes CNT and the graphene oxide GO, mixing the dispersions of the acid-treated carbon nanotubes CNT and the graphene oxide GO and stirring them to obtain a CNT-GO suspension, and filtering and drying the product to obtain a CNT-GO hybrid; (4) ball-milling the spherical copper powder in ethanol for the first time, then mixing the CNT-GO hybrid treated in step (3) with the ball-milled copper powder and ball-milling for the second time to obtain a composite powder, and then reducing the composite powder in a mixed atmosphere of Ar-H2 to obtain a CNT-RGO / Cu composite powder; (5) The CNT-RGO / Cu composite powder prepared in step (4) is subjected to spark plasma sintering to obtain a CNT-RGO / Cu composite material, which is a carbon nanotube-graphene / copper-based composite material.
2. The method for preparing the carbon nanotube-graphene / copper-based composite material having a discontinuous network structure according to claim 1, characterized in that: In the step (1), the purity of the carbon nanotubes CNT used is not less than 99%, the volume ratio of concentrated sulfuric acid to concentrated nitric acid is (3:1) to (5:1), and the acidification treatment time is 8 to 12 hours.
3. The method for preparing the carbon nanotube-graphene / copper-based composite material having a discontinuous network structure according to claim 1, characterized in that: In the step (2), the purity of the graphite powder used is not less than 99%.
4. The method for preparing the carbon nanotube-graphene / copper-based composite material having a discontinuous network structure according to claim 1, characterized in that: In the step (3), the volume ratio of the acid-treated carbon nanotubes CNT to graphene oxide GO is (3:1) to (6:1).
5. The method for preparing the carbon nanotube-graphene / copper-based composite material having a discontinuous network structure according to claim 1, characterized in that: In the step (3), the ultrasonic dispersion treatment time is 1 to 2 hours, the ultrasonic dispersion power is 10 kW, and the stirring time is 1 to 3 hours.
6. The method for preparing the carbon nanotube-graphene / copper-based composite material having a discontinuous network structure according to claim 1, characterized in that: In the step (4), the average particle diameter of the copper powder used is 1 to 3 μm, and the conditions for the first ball milling are: the ball-to-material ratio is 10:1, the diameter of the stainless steel balls is 5 to 7 mm, the ball milling speed is 250 to 350 r / min, and the ball milling time is 9 to 11 h; the conditions for the second ball milling are: the ball-to-material ratio is 10:1, the diameter of the stainless steel balls is 5 to 7 mm, the ball milling speed is 250 to 350 r / min, and the ball milling time is 4.5 to 5.5 h.
7. The method for preparing the carbon nanotube-graphene / copper-based composite material having a discontinuous network structure according to claim 1, characterized in that: In the step (4), the volume of CNT-GO accounts for 0.75% to 1.5% of the total volume of the CNT-RGO / Cu composite powder.
8. The method for preparing the carbon nanotube-graphene / copper-based composite material having a discontinuous network structure according to claim 1, characterized in that: In the step (4), the reduction temperature is 250-300° C. and the reduction time is 8-12 hours.
9. The method for preparing the carbon nanotube-graphene / copper-based composite material having a discontinuous network structure according to claim 1, characterized in that: In the step (5), the temperature during spark plasma sintering is set to 700-800° C., the heating rate is 100° C. / min, and the holding time is 10-15 min.
Citation Information
Patent Citations
High-oriented graphene-carbon nanotube mixed copper-based composite and preparation method thereof
CN109093108A
Preparation method of hydrogen etched carbon nanotube reinforced copper-based composite material
CN110894579A
Preparation method of graphene-carbon nanotube / copper-based composite material
CN112267040A
Copper-carbon composite powder and manufacturing method the same
KR1020160116112A